A prospective study to evaluate the clinical specificity of the cobas® MPX test kit for screening for HIV RNA, HCV RNA, and HBV DNA in blood donation samples using the cobas® 6800 system in HBV endemic areas - Lei Zhou; Lin Wang; Xiaofang Gong; Xiaochun Liu; Yaxuan Zou; Yingying Wang; Jinfeng Zeng; Liang Zang (Journal of Clinical Virology Plus)
Background: Nucleic acid testing (NAT) is widely used for screening blood donors for infectious diseases to enhance transfusion safety. Roche's advanced cobas® MPX assay detects human immunodeficiency virus (HIV), hepatitis C virus (HCV), and hepatitis B virus (HBV) using the cobas® 6800/5800 Systems, based on real-time PCR technology, providing improved sensitivity. This study aims to evaluate the clinical sensitivity and specificity of the cobas® MPX assay and its effectiveness in identifying infected donors in HBV endemic areas, particularly those with occult HBV infection (OBI). Materials and methods: A total of 12,067 donor samples from the Dalian Blood Center (DLBC, northern China) were tested for HIV, HCV, and HBV using both the cobas® MPX assay on the cobas® 6800 system and the previous generation cobas® TaqScreen MPX test v2.0 on the cobas s 201 system as the reference method. Testing was conducted using individual-donation testing (IDT) and primary pool of six donations (PP6), following the manufacturer's instructions and the operational procedures of the instruments. Samples with inconsistent results underwent repeated confirmation tests. Results: Cobas® MPX demonstrated 100.00 % overall percent agreement (95 % CI, 99.22 %-100.00 %) for IDT and 99.89 % (95 % CI, 99.82 %-99.95 %) for PP6. Kappa coefficients were 1.0 for IDT and 0.76 for PP6. Cobas® MPX specificity was 100.00 % (95 % CI, 99.22 %-100.00 %) for IDT and 99.99 % (95 % CI, 99.94 %-100.00 %) for PP6. Sensitivity was 100.00 % (95 % CI, 2.50 %-100.00 %) for IDT and 86.67 % (95 % CI, 68.36 %-95.64 %) for PP6. A total of 12 HBV NAT-yield cases were detected by cobas® MPX. Conclusion: Cobas® MPX demonstrated outstanding sensitivity and specificity in screening HIV, HCV, and HBV in routine blood donations, particularly enhancing occult HBV detection in endemic regions.